Factors Associated with Conjunctival Erosions after Ahmed Glaucoma Valve Implantation - Zhou, Di (J Ophthalmic Vis Res, 2018)
PURPOSE: To investigate the frequency of conjunctival erosions in a series of patients who underwent Ahmed valve implantation in a tertiary referral center and to study risk factors associated with the conjunctival erosions. METHODS: This is a single-center, retrospective case-control study of all patients who underwent Ahmed valve implantation between October 2006 and July 2016 at the Kresge Eye Institute in Detroit, Michigan. The series consisted of 306 eyes (277 patients) that underwent Ahmed valve implantation. The rate of conjunctival erosions was determined. Univariate, bivariate, and Cox-proportional hazard analyses were performed to identify factors associated with conjunctival erosions. RESULTS: During the study period, 23 erosions occurred in 306 eyes (7.52%). Aphakia was significantly more common in eyes with erosions (P < 0.05). Aphakia (P = 0.02), uveitic glaucoma (P = 0.03), and longer post-operative use of topical steroids (P < 0.04) significantly increased the risk of erosions based on the Cox model. There were similar rates of erosions with each type of patch graft. No conjunctival erosion was observed after using the modified scleral tunnel method (n = 10). CONCLUSIONS: The overall erosion rate was 7.52% in our series. Uveitic glaucoma, aphakia, and longer post-operative use of topical steroids were significantly associated with conjunctival erosions.